2014
DOI: 10.1097/01.prs.0000445107.08879.69
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 74

Abstract: nox-4 activity resulted in decreased hydrogen peroxide production and decreased production of oxidant inducible monocyte chemoattractant protein-1. ConClusions:These are the first reported results to demonstrate the significant contribution of dicer activity and miR production in promoting hemangioendothelioma growth in vivo. These are also the first reported results of miR21a-3p targeting nox-4 mRNA and inhibiting reactive oxygen species production in endothelial cells. Collectively, these results indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previously described methods for pedicle lengthening include vein grafts, arteriovenous loops, and arteriovenous bundle grafts. Recent studies have reported ALT flap pedicle length extension within the operative field [7-10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously described methods for pedicle lengthening include vein grafts, arteriovenous loops, and arteriovenous bundle grafts. Recent studies have reported ALT flap pedicle length extension within the operative field [7-10].…”
Section: Discussionmentioning
confidence: 99%
“…If the length of the ALT flap pedicle is insufficient despite adequate preoperative planning, pedicle length extension is required. Recent studies have reported pedicle length modification within the ALT operative field [7-10]. We attempted pedicle length extension with the distal descending branch in a case of insufficient pedicle length in the proximal direction because the perforator emerged from a quite proximal portion of the descending branch.…”
Section: Introductionmentioning
confidence: 99%